Rol de la SUNAT en el cumplimiento de obligaciones tributarias en empresarios de la ciudad de Iquitos año 2023 - Pachas Trujillo, Rosmery (2023)
The role of the entity in charge of the tax administration is essential for the development of the country, this function is aimed at facilitating compliance with tax obligations, however an important group of businessmen does not perceive this role positively, the study established as objective In general, to identify how the role of SUNAT in the compliance of tax obligations is perceived by businessmen in the city of Iquitos, for which I use a quantitative approach methodology, with an observational study and a descriptive non-experimental design including As a study sample of 60 businessmen located in the delimited spatial area, for data collection a questionnaire of closed questions was implemented with a statistical reliability of Cronbach's 0.942, obtaining as results that the majority of businessmen value the role of administration. of tax as adequate, to a lesser extent they consider it regular and a p lower percentage as inadequate, in the same way the study describes aspects related to the dimensions such as the guiding role in relation to guidance on the scope and application of regulations, procedures, development of talks and guidance to the taxpayer, in relation to the auditing role it is addressed aspects of procedures for information requirements, investigation, notifications, respect for principles, issuance of resolutions and supervisory power, as well as the role of collectors regarding means of declaration and payment, amount and tax pressure, coercive actions and limitations of business development.